2017
DOI: 10.1016/j.jare.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between different finite elements for elastic and aero-elastic analyses

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In a recent study, Mahran et al. 14 found that QUAD9NOD element is the best choice for aeroelastic analysis considering its efficiency and computational cost. Kuo 15 presented the effect of variable fiber spacing on the supersonic flutter of composite laminated plate.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Mahran et al. 14 found that QUAD9NOD element is the best choice for aeroelastic analysis considering its efficiency and computational cost. Kuo 15 presented the effect of variable fiber spacing on the supersonic flutter of composite laminated plate.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to its ability to discretize complex structures into small elements based on a geometric Computational Analysis for Design (CAD) model. In aeroelasticity, FEM can be applied to aerodynamics [42] or structures [3], and also its shape functions can be used in aeroelastic coupling [4]. The main point AMME-20 Journal of Physics: Conference Series 2299 (2022) 012005 is to select the appropriate element with the appropriate shape functions approximation for the required analysis.…”
Section: Aerodynamic and Structure Analysesmentioning
confidence: 99%
“…The main point AMME-20 Journal of Physics: Conference Series 2299 (2022) 012005 is to select the appropriate element with the appropriate shape functions approximation for the required analysis. Mahran et al compared five shell elements for aeroelastic analysis and found the 9-node quadrilateral element is the best and most accurate element among them [3]. In this comparison, they include the 3-node triangular element, 4-node quadrilateral element, modified 4-node quadrilateral element, 8-node element, and 9-node element.…”
Section: Aerodynamic and Structure Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this approximation, a blade is meshed as a 3D model, but it is modeled numerically in FE using quadrilateral element. It is found that higher-order elements such as nine-node element can obtain results more accurate than linear quadrilateral elements in elastic and aeroelastic analyses [8]. So, the element selection is also important.…”
Section: Blade Construction and Finite Element Analysismentioning
confidence: 99%